Handbook of Islamic Sects and Movements - Afzal Upal, Muhammad; Cusack, Carole M. (Brill Handbooks on Contemporary Religion, 2021)
The Handbook of Islamic Sects and Movements offers a multinational study of Islam, its variants, influences, and neighbouring movements, from a multidisciplinary range of scholars. These chapters highlight the diversity of Islam, especially in its contemporary manifestations, as a religion of many communities, theologies, and ideologies. Over five sections-on Sunni, Shia, Sufi, fundamentalist, and fringe Islamic movements-the authors provide historical overviews, analyses, and in-depth studies of large and small Islamic and related groups from all around the world. The contents of this volume will be of interest to both newcomers to the study of Islam and established scholars of religion who wish to engage with the dynamic label of Islam and the many impactful movements of the Islamic world.